Perception of Saudi dentists and lay people to altered smile esthetics - Nabeel Talic; Samar AlOmar; Asma AlMaidhan (Saudi Dental Journal)
Aim: To evaluate and compare the perceptions of Saudi dentists and lay people to altered smile features. Methods: Thirty-six digital smile photographs with altered features were used. Altered features included the following: crown length, width, gingival level of the lateral incisors, gingival display, midline diastema, and upper midline shift. The photographs were presented to a sample of 30 dentists and 30 lay people with equal gender distribution. Each participant rated each picture with a visual analogue scale, which ranged from 0 (very unattractive) to 100 (very attractive). Results: Dentists were more critical than lay people when evaluating symmetrical crown length discrepancies. Compared to lay people, Saudi dentists gave lower ratings to a crown length discrepancy of >2 mm (P < 0.001), crown width discrepancy of ⩾2 mm (P < 0.05), change in gingiva to lip distance of ⩾2 mm (P < 0.01), and midline deviation of >1 mm (P < 0.01). There was no significant difference between dentists and lay people towards alterations in the gingival level of the lateral incisors or towards a space between the central incisors. No significant sex difference was seen across the groups. Conclusion: In this sample, Saudi dentists gave significantly lower attractiveness scores to crown length and crown width discrepancies, midline deviations, and changes in gingiva to lip distance compared to Saudi lay people. Keywords: Saudi dentists, Smile esthetics, Perception, Lay people